Activation of chaperone-mediated autophagy as a potential anticancer therapy - Galan-Acosta, Lorena (Autophagy, 2015)
Chaperone-mediated autophagy (CMA), a subtype of autophagy, delivers select proteins into the lysosome for degradation. Defects in CMA activity have previously been linked with neurodegenerative diseases due to the accumulation of misfolded proteins, but the role of CMA in cancer is currently not well defined. In a recent study, we provide a novel mechanism by which excessive activation of CMA can be exploited as a method to eliminate cancer cells by inducing metabolic catastrophe and delineate a novel strategy to promote the degradation of HK2 (hexokinase 2) in cancer cells.